THE IMPORTANCE OF ASSESSING FORMATIVE ASSESSMENT OF STUDENTS OF BUDDHIST RELIGIOUS EDUCATION: PENTINGNYA PENILAIAN FORMATIF DOSEN TERHADAP MAHASISWA PENDIDIKAN KEAGAMAAN BUDDHA - Sutikno, Yadi (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2019)
Formative assessment is carried out to continue the learning of students during the learning process, then to provide feedback (feedback) for the improvement of the learning program. This research uses the qualitative type of literature study (library research). Formative assessment can improve student learning or lectures. Six key elements informative discussion are cultural class discussion that can support conversation and use of discussion, plan learning and support students in achieving these goals, use appropriate learning methods to meet diverse student needs in the class, use respect for student understanding, provide feedback towards students and adjust learning according to the needs of students in class, and active involvement of students in the learning process. Based on this opinion, every Buddhist lecturer can use Formative Forms to improve the results of his lectures. This means that it is really important to be done by lecturers of Buddhist Education students.